2021
DOI: 10.1097/meg.0000000000002157
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal bacterial overgrowth and orocecal transit time in patients of nonalcoholic fatty liver disease

Abstract: Background: To explore the frequency of small intestinal bacterial overgrowth (SIBO) and orocecal transit time (OCTT) in patients with nonalcoholic fatty liver disease (NAFLD). Methods: 103 patients with NAFLD and 49 healthy controls were enrolled. Clinical indicators such as body mass index (BMI), liver function, blood lipids, HOMA-IR, serum endotoxin of NAFLD patients were collected and examined. Fibro Touch was used to detect the (controlled attenuation parameter) CAP and liver stiffness measurement (LSM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In this context, our results are in line with the results of the study by Guimaraes et al, who reported that the prevalence of SIBO among histologically confirmed NAFLD patients using the lactulose breath test as a diagnostic modality was 26.2% [ 32 ]. Different reports in the literature, both in NAFLD [ 33 , 34 , 35 ] and in NASH [ 36 ] patients that used either cultures of jejunal aspirates [ 33 , 34 , 36 ] or a lactulose breath test [ 35 ] to diagnose SIBO, reported an even higher prevalence of the syndrome, highlighting its frequent occurrence in this population. Specifically, SIBO prevalence was reported to be 40% among NASH individuals [ 36 ], while it approached or exceeded 35% in those with NAFL [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, our results are in line with the results of the study by Guimaraes et al, who reported that the prevalence of SIBO among histologically confirmed NAFLD patients using the lactulose breath test as a diagnostic modality was 26.2% [ 32 ]. Different reports in the literature, both in NAFLD [ 33 , 34 , 35 ] and in NASH [ 36 ] patients that used either cultures of jejunal aspirates [ 33 , 34 , 36 ] or a lactulose breath test [ 35 ] to diagnose SIBO, reported an even higher prevalence of the syndrome, highlighting its frequent occurrence in this population. Specifically, SIBO prevalence was reported to be 40% among NASH individuals [ 36 ], while it approached or exceeded 35% in those with NAFL [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different reports in the literature, both in NAFLD [ 33 , 34 , 35 ] and in NASH [ 36 ] patients that used either cultures of jejunal aspirates [ 33 , 34 , 36 ] or a lactulose breath test [ 35 ] to diagnose SIBO, reported an even higher prevalence of the syndrome, highlighting its frequent occurrence in this population. Specifically, SIBO prevalence was reported to be 40% among NASH individuals [ 36 ], while it approached or exceeded 35% in those with NAFL [ 33 , 34 , 35 ]. Moreover, among individuals with biopsy-proven NASH, the prevalence of SIBO was >43% both in those with concomitant metabolic syndrome as well as in those without [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All those factors might be implicated in the development of NAFLD. A high prevalence of SIBO is observed in NAFLD population [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. SIBO, by inducing an immunological fluctuation, could lead to chronic inflammation, mitochondrial disorders, a cumulation of lipids in hepatocytes, and NASH.…”
Section: Discussionmentioning
confidence: 99%